Novos livros, novos poemas: adaptações de Odilon Moraes de Ismália e conselho - Almeida, Beatriz Pereira de (2022)
Telling and retelling stories is part of our daily lives. In literature, this is no different. Over time, the stories were adapted according to the authors' intention, undergoing adaptations to fit into a certain context of reception and this practice remains present today. In this sense, we observe that picturebook authors use this practice to expand what is received by children. Odilon Moraes is one of these authors, since, through the picturebook, he created new works from existing poems: Ismália, by Alphonsus de Guimaraens and Conselho, by Fernando Pessoa. Without changing the verbal text, Moraes added illustrations to the poems and a new graphic project, modifying their support, transforming them into a new artistic object and, consequently, changing or, at least, expanding the readership. Therefore, throughout this research, we will have as a general objective to analyze the adaptation process in the works Ismália and Conselho, illustrated by Odilon Moraes, seeking to identify the mechanisms used by the illustrator to “recreate” such poems, such as illustrations, materiality and the overall graphic design of the books. This research is qualitative, it has bibliographic and documentary research as methodological procedures. Furthermore, to theoretically support it, we selected authors such as Oliveira (2008), Linden (2011), Nikolajeva (2011), to discuss about the picturebook, Zilberman (1994) and Hutcheon (2013), in relation to the adaptation and the adaptation of works to a new audience, Darnton (1986), Lajolo and Zilberman (2007) and Zilberman (2014) about the process of consolidation of European and Brazilian children's literature.